What kinds of social network groups do teachers find useful? - Kelly, Nick; Dawes, Les; Whiteford, Chrystal; De Laat, Maarten; Corbett, Genevieve; Robertson, Amanda (Proceedings of the International Conference on Networked Learning, 2024)
This paper presents results from a survey of teachers describing their two most useful Facebook groups (n=108 teachers). It addresses a gap in the literature, in that many studies investigate teachers within certain Facebook groups, but little is known about the types of groups that teachers-who-use-Facebook find to be most useful. Analysis of the survey results looks at the privacy, thematic focus, and regional focus of groups that teachers report to be useful. The study also addresses the question of “what kinds of peer support do teachers find within these useful Facebook groups?” The results show that useful Facebook groups tend to be private, positioned at a state/jurisdiction/national level, and have a clear thematic focus. Results also show that within these useful Facebook groups teachers report high levels of pragmatic support, with lower levels of modelling of practice, reflection and feedback, meaningful connections, and emotional support (in that order). The paper discusses the significance of these findings with respect to issues of policy, design, and facilitation of Social Network Sites (SNSs) as well as teacher preparation for competencies to thrive within SNSs.